Morfometria da alta bacia do rio Passa Cinco (SP) - Andrade, Rafael Vilela de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This research consisted on an analysis of the relation between tectonic and erosive processes in the evolution of the cuesta system using morphometric techniques. The basaltic cuesta identified in São Paulo territory corresponds to forms of relief that separate the high lands of the Western Plateau from the lowlands of the Peripheral Depression (ALMEIDA 1974). However, it is not possible to analyze the entire cuesta system. Therefore, a small area containing this feature was chosen, corresponding to the Upper Rio Passa Cinco Basin, a sub basin of the Corumbataí River in the interior of the state of São Paulo. The intention was to understand how the process of relief evolution occurs in this region, relating the erosive processes to the influences of tectonism. For such, morphometric techniques were used based on the elaboration of several maps of the basin, in order to collect quantitative data about the forms and processes that operate on the site. As a result, it was possible to identify strong conditioning of the structural elements on the erosive dynamics in that area, providing a better understanding of the dynamics of cuesta relief in the region

Esta pesquisa consistiu em uma análise a respeito da relação entre os processos tectônicos e erosivos na evolução do sistema de cuestas segundo técnicas morfométricas. As cuestas basálticas identificadas no território paulista correspondem a formas de relevo que separam os terrenos elevados do Planalto Ocidental das terras rebaixadas da Depressão Periférica (ALMEIDA 1974). O estudo realizado, entretanto, não possibilita que o sistema de cuesta seja analisado em sua totalidade. Portanto foi selecionada uma pequena área que abriga essa feição, correspondente a Alta Bacia do Rio Passa Cinco, uma sub bacia do Rio Corumbataí no interior paulista. Dessa forma, buscou-se compreender como se dá o processo de evolução do relevo na região, relacionando os processos erosivos com as influências do tectonismo. Para tanto, foram utilizadas técnicas morfométricas baseadas na elaboração de diversos mapeamentos da bacia, com o intuito de levantar dados quantitativos a respeito das formas e dos processos atuantes sobre o local. Como resultado, foi possível identificar forte condicionamento dos elementos estruturais sobre a dinâmica erosiva da bacia, proporcionando uma melhor compreensão sobre a dinâmica do relevo de cuestas na região
Keywords: Morfometria; Bacias hidrográficas; Erosão; Cuestas; Cuesta basáltica; Relevo (Geografia); Mapeamento geomorfológico; Geomorfologia; São Paulo (Estado); Corumbataí, Rio, Bacia (SP)